Communication Lab : English for IT. - Cornette, Femke, 1990- (Gent : Owl Press, 2021)
This book deals with multiple situations in which IT students may find themselves during their professional careers and focuses on the various skills that are required when having to use a second language during said career. All units are centered on one IT-related topic and contain exercises on skills such as listening, reading, writing and speaking. The book contains many topical articles, podcasts and videos. The emphasis in the first six units is on telephone conversations/(client) meetings and writing professional documents, whereas the six final units mainly focus on writing a paper and presentation skills. Each unit also contains one final case study in which all acquired skills are put to use.
Keywords: english